Black Skin, White Uniforms: Race, Clothing, and the Visual Vernacular of Luxury in the Andes. Issue 2 (3rd April 2017) - Walker, Tamara J.
Abstract : In a 2011 article in Hola! magazine, several members of a wealthy Colombian family posed on the terrace of their expansive estate overlooking the Valley of Cauca. It was a striking image, in part because it featured an all-female lineup of mothers and daughters who were all power-players in the local business community. But it was the figures in the background of the image that stood out most of all: posed in profile were two Afro-Colombian women dressed in all-white uniforms and holding serving trays. The image adhered to and called forth a visual tradition that dated back to the region's slaveholding past, when masters and slaves appeared together in various genres of portraiture. These images persisted even as slavery gave way to freedom, with members of elite families in the Andes posing for cameramen in the company of their black domestic servants. In tracing the contextual and conceptual origins of the photograph that appeared in Hola! magazine, this article it not only signals just what central figures African-descent servants have always been to the visual culture of the Andes, but also highlights the utility of visual culture to understanding discourses of race in the region.